Consumer Behavior in the E - Commerce Era - Sriwanti Belani; Hadiyati, Rini (Penelitian dan Pengembangan Ilmu, 2024)
This research investigates the relationship between factors such as accessibility, social media influence, personalization, user satisfaction, customer retention strategies, and consumer behavior in the context of e-commerce. Through a systematic literature review, the authors explore how these factors influence the way consumers search for information, evaluate options, and make purchasing decisions in an electronic commerce environment. The results show that there is a significant relationship between these factors and consumer behavior in e-commerce, with relevant implications for companies' marketing and sales strategies in the digital era.